Double Reflections in Polarized Radar Data Reveal Ice Fabric in the North East Greenland Ice Stream - Niels F. Nymand; David A. Lilien; Tamara A. Gerber; Christine S. Hvidberg; Daniel Steinhage; Prasad Gogineni; Drew Taylor; Dorthe Dahl‐Jensen (Geophysical Research Letters)
Abstract The orientation of ice crystals within large ice masses has a strong influence on their mechanical properties, but cannot be directly observed from the surface. The bulk birefringence of anisotropic ice allows us to infer information about the crystal orientation fabric (COF) from polarized radar measurements. Here, we show a new approach for determining the orientation and strength of horizontal COF anisotropy from two radar reflections originating from the same physical layer in birefringent ice. We apply this method to data collected as part of a ground‐based radar survey of the North East Greenland Ice Stream. We observe a 12‐degree clockwise rotation of the fabric at the center of the ice stream, and a tendency toward a flow‐aligned COF further southeast. This asymmetry across the ice‐stream centerline adds to growing evidence for a more variable ice stream than previously assumed.